Students’ Perception of the Use of English Application “Simpler” for Improving Vocabulary Skills in Young Learners - Megasari, Fritha; Fitri, Anisa; Febrian, Raka; Saputra, Andika (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
Vocabulary is one of the important aspects connected to the four skills of English. To master all those skills, learners should achieve this skill. Vocabulary learning became an obstacle that was faced by learners in the teaching and learning activities, especially young learners. Young learners became a challenge in English learning and teaching because of their young age. Their short concentration, lack of attention, and being easily bored, encouraged the researcher to utilize learning media as a tool to enrich their English learning and teaching, preferably in vocabulary learning. Therefore, the researcher wants to use a conventional technology that can contribute to the ease of teaching and learning vocabulary. Simpler application is one of the number of applications used to enhance English language acquisition. The objective of this research was to explore students’ perception of the use of Simpler application as a learning media for improving vocabulary skills in young learners. The research was conducted using a qualitative design. By adapted questionnaires that were developed by Saraswati, et. al. (2021). The subject of the research is young learners around the age of 11-12 years old. The result that showed in this research is Simpler application, an effective learning media to enhance elementary school young learners’ vocabulary skill and can be applied as a learning media that were implemented in English teaching and learning process.